Number-size distributions of atmospheric aerosol particles (10<D_p<365nm) at Ny-Alesund, Norwegian Arctic : Their relationship with air mass history - ニシタ, チハル; オサダ, カズオ; ハラ, ケイイチロウ; キドウ, ミズカ; ワダ, マコト; シバタ, タカシ; イワサカ, ヤスノブ; Nishita, Chiharu; Osada, Kazuo; Hara, Keiichiro; Kido, Mizuka; Wada, Makoto; et al. (National Institute of Polar Research, 2001)
P(論文) Number-size distributions of aerosol particles between 10 and 365nm in diameter were observed at Ny-Alesund, Norwegian Arctic from 18 to 29 February 2000 together with concentrations of SO_2 and NH_3,and Na^+ and non-sea-salt SO_4^<2-> in non-size-segregated particles. The observed particle size distributions and concentrations were fitted by lognormal distributions and interpreted with respect to air mass histories that have different origins. Maximum concentration of aerosol particles was predominantly found in the accumulation range (150<D_p<200nm) for all times except for air masses influenced by local air pollution. Concentrations of SO_2 and SO_4^2 correlated well with concentrations of aerosol particles in the accumulation range. The number-size distributions of aerosol particles in Arctic air masses derived from industrialized regions in mid-latitudes through the ice packed Arctic Ocean showed an interesting feature, a bimodal pattern with modes at Aitken and accumulation size range. Number concentrations of particles in the air masses from the North Atlantic Ocean were lower than that in air masses from other regions. departmental bulletin paper